An efficient strategy for the extraction and purification of lignans from Schisandra chinensis by a combination of supercritical fluid extraction and high‐speed counter‐current chromatography. Issue 24 (18th November 2013) - Chu, Chu; Zhang, Shidi; Tong, Shengqiang; Li, Xingnuo; Yan, Jizhong
<x xml:space="preserve">Abstract</x> An efficient strategy for extracting and separating five lignans from Schisandra chinensis (Turcz.) Baill has been developed using supercritical fluid extraction (SFE) and high‐speed counter‐current chromatography (HSCCC) in the present study. First, the extraction was performed by a preparative SFE system under 15 MPa of pressure at 36°C for 4 h. Then, the SFE extract was successfully separated and purified by HSCCC with a two‐phase solvent system composed of n‐hexane/ethyl acetate/methanol/water (6:4:5:5, 6:4:6:4, 6:4:8:2, v/v) in a stepwise elution mode. The fractions were analyzed by HPLC, and the chemical structures of the products were identified by ESI‐MS and 1H NMR spectroscopy. As a result, a total of 12.5 mg of schisandrin at 98.0% purity, 7.1 mg of gomisin A at 98.1% purity, 1.8 mg of schisantherin B at 93.3% purity, 4.4 mg of deoxyschisandrin at 92.9% purity, and 6.8 mg of γ‐schisandrin at 89.1% purity were obtained from 300 mg crude extract in a one‐step purification.